Enriching human-robot interaction with mobile app in interventions of children with autism spectrum disorder - Zorcec, T; Ilijoski, B; Simlesa S; Ackovska, N; Rosandic M; Popcevic K; Robins B; Nitzan N; Cappel D; Blum R (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/ Sciendo, 2021)
Introduction: Autism spectrum disorder (ASD) is a group of complex lifelong neurodevelopmental disorders, characterized by difficulties in social communication and stereotyped behaviours. Due to the increasing number of children with ASD, it is important to continue developing interventions as well as invent new ones. Human-robot interaction can contribute to better outcomes for these children. There are several robots such as Nao, Kaspar, ZENO, Probo, ZECA, etc. which are used in autism interventions. Many mobile and web applications are in constant growth, too. They target skills such as collaboration, social skills, language skills, social competence, and communication. Aim: To explore the usability of the humanoid robot Kaspar and a complementary app in interventions of children with ASD. Sample: 20 children with ASD, aged between 23 and 76 months old. Method: As an added intervention for this group of children, we used the robot Kaspar and its complemen tary app. Kaspar is a child-sized humanoid robot that uses bodily expressions, facial expressions, gestures, and pre-recorded speech to interact with a human. Results: This intervention achieved certain positive shifts in eight of the eleven measured developmental domains, such as communication functions and means, turn taking, imitation, language skills, play, atten tion and daily life skills. The three categories that had inconsiderable improvement are vocalization and speech, cause and effect and coping skills. Conclusion: Based on the measurements before and after the use of Kaspar and its complementary app, there is improvement, primarily in the domains of language, imitation and communication skills and attention.
Keywords: autism spectrum disorder; children; robot and mobile app intervention